Studi Pendahuluan Biosensor Berbasis Magneto-Impedansi: Wahyu eko prastyo, N Nuryani, Budi Purnama - Wahyu Eko Prastyo Wahyu Eko Prastyo; Nuryani Nuryani; Budi Purnama Budi Purnama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
Bio-impedance multilayer sensor [NiFe(800)/Cu(300)]4 has been successfully fabricated by electro deposition method. The bio-magneto-impedance response is defined as the impedance change due to the applied field (MI) with and without the meat. The bio-MI response profile of beef samples has a similar to the magneto-impedance curve and depends on the measurement frequency. The bio-MI response in this study is 0.7% at 100 kHz.